SIFAT, KEPRIBADIAN, TUJUAN HIDUP MAHASISWA, DAN KAITANNYA DENGAN PERSEPSI TENTANG PERGAULAN LAWAN JENIS - Monika Yuliantin; Herien Puspitawati; Megawati Simanjuntak (Jurnal Ilmu Keluarga dan Konsumen, 2010)
Globalization that develops in line with development of science and technology such as film, soap opera, and music do not only give positive influence but also have brought negative influence for Indonesian people who still extremely hold norms especially religion norm. The aimed of this research was to analyze the perception about interaction of opposite gender of college students. This research used cross sectional study design. The research was done in Bogor Agricultural University (IPB) Bogor. Respondents of this research were 146 students of undergraduate of 2nd and 3rd grade in the year 2008, consist of 43 men and 103 women. Almost all of respondents had conservative perception about interaction of opposite gender. The study found significant correlation between: (1) respondents perception about interaction of opposite gender with type of gender, cumulative achievement index, trait and personality, (2) interaction of opposite gender respondents’ behaviour with type of gender, trait and personality, monthly pocket money, and respondents’ perception about interaction of opposite gender. Multiple regression analysis showed that type of gender and trait and personality variables had significant effect on perception of interaction of opposite gender.